THE IMPORTANCE OF GAME TECHNOLOGIES IN ENGLISH LESSONS FOR PRIMARY SCHOOL STUDENTS. - Maxmudova Nilufar, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: In English lessons in primary schools, game technologies play an important role in making the learning process more interesting and effective. Through games, students actively participate in the language learning process, which increases their motivation and helps them better absorb new information. Game technologies, such as interactive programs, mobile applications and online platforms, provide students with the opportunity to communicate with each other in the process of language learning. This annotation discusses the importance of game technologies in English lessons in primary schools, their impact and benefits.